Nostalgiczny spacer po ulicy Nowe Miasto, czyli Kolbuszowa we wspomnieniach matki Janka Bytnara = A nostalgic walk along New Town Street, or Kolbuszowa in memories of Janek Bytnar's mother - Karkut, Dorota (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Zdzisława Rechul's (Janek Bytnar's mother) personal memories are directly related to the town of her birth and childhood ? Kolbuszowa. They recall the events from the everyday life, describe the places and characters associated with the local history. They affect the identity of the individual and the local group.
Keywords: wspomnienia; pamięć miejsca; Kolbuszowa - historia; Rechul-Bytnar, Zdzisława (1901-1994); memories; memory of the place; the history of Kolbuszowa